HSABC Algorithm for Economic Operation Emission Based - AN Afandi; Farrel Candra Winata Afandi (Fakultas Teknik Universitas Bhayangkara, 2023)
The total cost of maintaining the energy infrastructure is one of the most important problems. Technically, this issue considers the fuels and emissions of generating units working within specific parameters in an Economic Operation Emission Based (EOEB). This study evaluates the performance of the Harvest Season Artificial Bee Colony (HSABC) Algorithm in search of the best EOEB solution. To compute the EOEB issue on the IEEE-62 bus system, simulation programming techniques are applied based on HSABC Algorithm. The simulation findings indicate that the investigated approaches have a range of characteristics, speed, starting, and statistical value values.